Developing microservices with Node.js : learn to develop efficient and scalable microservices for server-side programming in Node.js using this hands-on guide /: learn to develop efficient and scalable microservices for server-side programming in Node.js using this hands-on guide. (2016) - Gonzalez, David
No abstract available